Social Support and Quality of Life in Individuals with Injections Drug Use Having Comorbid HIV/ AIDS Infection - Wajeeha Riaz, Zaeema Riaz (Pakistan Journal of Psychology, 2019)
The objective of the present study was to investigate the predictive association between Social Support from Significant Others, Family, and Friends and Quality of Life (QOL) in individuals with comorbid substance use disorders and HIV/AIDS infection. The participants of the current study comprised of 150 males with Injection Drug Use (IDU) having comorbid HIV/AIDS infection, which were selected from a treatment unit of SACP (Sindh Aids Control Program) in Karachi. Participants’ age ranged from 18 to 58 years (Mean=29.7, SD=6.74). The measures used along with Demographic Information Sheet include: Urdu version of Multi-dimensional Scale of Perceived Social Support (MSPSS) (Rizwan & Aftab, 2009) and WHO-Quality of Life Scale (WHOQOL-BREF) (Khan, Akhter, Ayub, Alam & Laghari, 2003). The results of Multiple Regression Analysis reflect social support from all three sources i.e. significant others, family and friends to be significant predictors of quality of life. Thus it is concluded that provision of social support to individuals with IDU having comorbid HIV/AIDS is crucial in enhancing their QOL.